Linguistics as Metaphor in Organizational Regularization and Decay - Mentzer, Marc S. (American Journal of Management, 2020)
Linguists have found that the twin tendencies of regularization and decay lead to the development of language structures that are simultaneously complex and unstable. This serves as a metaphor to illuminate the parallel processes of regularization and decay in organizational structure. Both the evolution of languages and the evolution of organizational structures reflect the desire to minimize cognitive work, as shown in the embracing of cognitive order while simultaneously seeking the course of least resistance.